A Review of Sustainable Materials to Improve Geotechnical Properties of Soils - Al-naje, Farah Qais; Abed, Alaa Hussein; Al-Taie, Abbas Jawad (Al-Nahrain Journal for Engineering Sciences, 2020)
Most of the soils suffered from significant geotechnical problems dependent on factors like the type of soil, soil composition and mineralogy. Specifically, the problems related to mechanical and physical properties of soils. Several studies have been used to mitigate the adverse effects of soils through using either additive conventional materials such as cement, lime or these soils blending with produced material and chemical materials. This paper focuses on stabilizing or improving different soils using sustainable materials. These materials provided environmental and economic benefits while mitigating a health hazard, storage problems, and a potential pollution source. They can be classified according to these sources into four groups: industrial waste (by-products), agriculture waste, domestic waste and mineral waste. According to the results of this review, compaction characteristics, California bearing ratio and unconfined compressive strength have been studied and discussed in this paper.